2008
DOI: 10.1016/j.bbrc.2008.02.102
|View full text |Cite
|
Sign up to set email alerts
|

Profiling TRA-1-81 antigen distribution on a human embryonic stem cell

Abstract: Human embryonic stem (hES) cells hold great promise in regenerative medicine. Although hES cells have unlimited self-renewal potential, they tend to differentiate spontaneously in culture. TRA-1-81 is a biomarker of undifferentiated hES cells. Quantitative characterization of TRA-1-81 expression level in a single cell helps capture the "turn-on" signal and understand the mechanism of early differentiation. Here we report on our examination of TRA-1-81 distribution and association on a hES cell membrane using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…It may be used to obtain ultrastructural details of biological samples with high resolution and measure the force within and between single biomolecules (Hu et al, 2008;Kienberger et al, 2006;Lee et al, 2007;Pranav et al, 2008;Qiu et al, 2008;Vincent et al, 2009;Yersin et al, 2007). As such, we obtained the nanostructure of SSCs by AFM and β1-integrin antibody functionalized AFM tip was used to detect complementary receptors on cellular surface to map the distribution of β1-integrin at nanometer level, these results provide a new insight into the nano-biology of β1-integrin expression on SSCs membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It may be used to obtain ultrastructural details of biological samples with high resolution and measure the force within and between single biomolecules (Hu et al, 2008;Kienberger et al, 2006;Lee et al, 2007;Pranav et al, 2008;Qiu et al, 2008;Vincent et al, 2009;Yersin et al, 2007). As such, we obtained the nanostructure of SSCs by AFM and β1-integrin antibody functionalized AFM tip was used to detect complementary receptors on cellular surface to map the distribution of β1-integrin at nanometer level, these results provide a new insight into the nano-biology of β1-integrin expression on SSCs membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies on the spontaneous differentiation of hESCs used a high serum concentration with DMEM media in the presence of non-essential amino acids without additional growth factors [12]. When gelatin or matrigel were used as a matrix, the medium allowed rapid spontaneous differentiation into all three lineages with no specification.…”
Section: Introductionmentioning
confidence: 99%
“…Pluripotent hESCs have the potential to become any type of cell in our body, but all pluripotent cells may not have the same expression level of the various stem-cell markers (Stewart et al 2006). For example, Qiu et al (2008) demonstrated that expression of Tra-1-81 receptors varies significantly even among stem cells from the same line (Qiu et al 2008). Future experiments to determine expression level of receptors on the surface could help determine whether this as a potential source of the difference in capture efficiency.…”
Section: Discussionmentioning
confidence: 94%
“…Although undifferentiated hESC markers are well characterized, it is also clear that there exists significant heterogeneity between hESC lines and even within pluripotent hESC populations from the same line with respect to the levels of expressed proteins (Gu et al 2010;Mantel et al 2007;Qiu et al 2008;Stewart et al 2006). Pluripotent hESCs have the potential to become any type of cell in our body, but all pluripotent cells may not have the same expression level of the various stem-cell markers (Stewart et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation